2020
DOI: 10.31234/osf.io/v84mr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rehearsing post-Covid-19 citizenship: Social representations of UK Covid-19 mutual aid

Abstract: People across the world have responded to the pandemic by mobilising and organising to support their communities, setting up mutual aid groups to provide practical, financial, and social support. Mutual aid means short-term ‘crisis response’ for some, while for other groups, it is a chance to radically restructure society, and what it means to be a member of that society. We applied a social representations lens to examine the ways in which citizenship was understood and performed by members of UK Covid-19 mut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…These groups focused on building bottom-up structures of cooperation and horizontal networks of solidarity ( Whitley, 2020 ), which represents a radical divergence from traditional public services and forms of volunteerism ( Spade, 2020 ). Many different acts of solidarity during the COVID-19 crisis have been reported, including grocery shopping and delivery, food parcel deliveries, collection of prescriptions, dog walking, postcard and library services, emotional support by telephone/email helpline, informational support on existing public services, community gardening, and more ( O’Dwyer et al, 2020 ; Tiratelli and Kaye, 2020 ; Mao et al, 2021 , in press ). Most of the published research on COVID-19 mutual aid groups has been descriptive (see Mao et al, 2021 for a review).…”
Section: Community Solidarity In the Covid-19 Pandemicmentioning
confidence: 99%
“…These groups focused on building bottom-up structures of cooperation and horizontal networks of solidarity ( Whitley, 2020 ), which represents a radical divergence from traditional public services and forms of volunteerism ( Spade, 2020 ). Many different acts of solidarity during the COVID-19 crisis have been reported, including grocery shopping and delivery, food parcel deliveries, collection of prescriptions, dog walking, postcard and library services, emotional support by telephone/email helpline, informational support on existing public services, community gardening, and more ( O’Dwyer et al, 2020 ; Tiratelli and Kaye, 2020 ; Mao et al, 2021 , in press ). Most of the published research on COVID-19 mutual aid groups has been descriptive (see Mao et al, 2021 for a review).…”
Section: Community Solidarity In the Covid-19 Pandemicmentioning
confidence: 99%
“…Perceived group politicization was also related to lower coping self‐efficacy and higher anxiety. Other work has found that members of mutual aid groups conceptualize their work as apolitical due to the potential to alienate potential or current members or cause conflict (O'Dwyer et al, 2020 ). It seems plausible that a majority of our participants here also took such a view of the work done by their groups, given the way in which perceived group politicization was related to less positive group perceptions and poorer self‐reported psychological functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Organized generally on a hyper‐local basis and via social media, these groups fulfilled practical tasks such as grocery shopping and collecting medication, but also provided invaluable emotional support and advice to members of the community, many of whom were struggling with physical and mental health issues as well as an economic disadvantage (Jones et al, 2020 ). Without mutual aid groups, vulnerable people would have had to rely on assistance from the local government, which was frequently perceived as too slow or inadequate in its provision (O'Dwyer, Beascoechea‐Seguí, & Souza, 2020 ; Tiratelli & Kaye, 2020 ).…”
Section: Covid‐19 Mutual Aid Groupsmentioning
confidence: 99%
“…These groups focused on building bottom-up structures of cooperation and horizontal networks of solidarity (Whitley, 2020), which represents a radical divergence from traditional public services and forms of volunteerism (Spade, 2020). Many different acts of solidarity during the COVID-19 crisis have been reported, including grocery shopping and delivery, food parcel deliveries, collection of prescriptions, dog walking, postcard and library services, emotional support by telephone/email helpline, informational support on existing public services, community gardening, and more (O'Dwyer et al, 2020;Tiratelli and Kaye, 2020;Mao et al, 2021, in press). Most of the published research on COVID-19 mutual aid groups has been descriptive (see Mao et al, 2021 for a review).…”
Section: Community Solidarity In the Covid-19 Pandemicmentioning
confidence: 99%
“…Indeed, a rapid review of the literature available up to October 2020 showed that social networks and connections, local knowledge and social trust were key dimensions associated with COVID-19 community organizing and volunteering (Mao et al, 2021). Further recent studies have examined social psychological processes in COVID-19 community solidarity groups, by looking for instance at participants' representations of citizenship (O'Dwyer et al, 2020), and the role of community identity as a predictor of providing COVID-19 help among volunteers (Wakefield et al, 2021). Cocking et al (in preparation) concluded that mutual aid groups were based on a mixture of social capital and new emergent groups that evolved in response to participants' desire to create new forms of identification with one's own neighborhood or street.…”
Section: The Dynamics Of Solidarity In Extreme Eventsmentioning
confidence: 99%